Māsas Marijas Stefanas Ideju Aktualitāte Mūsdienu Latvijas Katoļu Tradīcijā: The Relevance of Sister Marija Stefana. - Berzinska, Lilija (Cel̜š, 2012)
This publication focuses on Sister Marija Stefana of The Poor Jesus Child Congregation and her ideas in the 21st century Latvian Roman Catholic tradition. The aim of the article is not only to show Sister Marija Stefana as an outstanding representative of the Roman Catholic Church of Latvia, who created and developed her own teaching and approach towards spiritual and theological issues, but also draw attention to her public image. Created and shaped by spiritual authorities of the Catholic Church of Latvia that image is nothing more than Latvian version of the French saint Thérèse of Lisieux and continuation of the teaching and phenomenon of the French saint. That is why it is extremely important to find the real message and personality of Sister Marija Stefana, considering the important role she plays in Latvian Catholic tradition and popularity among believers.